PENGARUH BRAND IMAGE DAN E-WOM TERHADAP MINAT BELI SKINCARE SOMETHINC PADA SHOPEE - Tarigan, Arihta; Gunawan, Yesha (Universitas Nusa Cendana, 2024)
Information technology's advancement has significantly impacted how people communicate, do business, and shop. A platform called Shopee is available to assist consumers with their online transactions. The category with the highest sales on Shopee is beauty and skincare which makes the trend in beauty products. A local brand called Somethinc is active on Shopee and uses positive Brand Image and Electronic Word of Mouth (eWOM) to leverage this trend as a marketing tactic. This study aimed to determine the relationship between Brand Image, Product Rating, Product Review, and Purchase Intention. This research uses a quantitative method with a Google Forms questionnaire distributed through social media. This study used SPSS 26 to process data from 130 respondents who satisfied requirements such as age and Jabodetabek residence. The results of this study indicate that Brand Image, Product Rating, and Product Review have a significant impact on Purchase Intention. Keywords: Brand Image; Electronic Word of Mouth; Product Rating; Purchase Intention